Melirik Ciri Khas Batik Lasem - RA Sekartaji Suminto (Institut Seni Indonesia Yogyakarta, 2015)
Batik is a priceless cultural heritage of the Indonesian archipelago. Many parts of Indonesia has a batik tradition, especially Java and its surounding areas. Batik has been known since centuries ago. Batik is classsified into two major types, namely inland and coastal batik. Batik Lasem is one of the famous coastal batik textiles which has some special features characterizing batik Lasem. Blood red color that can only produced by the roots of Mengkudu tree from Lasem is one of characteristic of batik Lasem. Similarly, Pusung Tumpal motif is still maintained until now. Maintaining the hallmark is the effort to preserve the quality and beauty of batik, in this case is batik Lasem. Keywords: Batik Lasem, blood red, tumpal pusung, hallmark